Milliyetçi Hareket Partisi’nin 2017 anayasa referandumu süresi boyunca sosyal medyada kullanmış olduğu iletişim dilinin incelenmesi - Kaymaz, Tuğba (İstanbul Bilgi Üniversitesi, 2017)
[Abstract Not Available]
Investigation of communication license used in the social media during the constitutional reference during the 2017 constitutional National Movement Party